Analisis Praktik Pembiayaan Murabahah Pada Bank Syariah Mandiri Tanjungpinang Kepualauan Riau - Sanusi, Makhda Intan; Setiawan, Indra; Aminudin, Agung (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
Nowadays, there are many financial institutions that adhere to sharia principles, both micro and macro, both in the form of bank and non-bank Islamic financial institutions. These financial institutions have their respective roles and operations. Bank Syari'ah Mandiri (BSM) is a financial institution whose operational system is based on sharia principles which are based on the Al-Qur'an and Hadith. Where the main task is to collect funds from people who have more funds and distribute them to people who need them. Sharia banks also provide services. One of the sharia financial institutions in Tanjungpinang is BSM Tanjungpinang. BSM Tanjungpinang offers several fund distribution products, including muraabahah financing, which is most popular with customers. This research uses qualitative research, namely research procedures that produce descriptive data in the form of words. Data analysis carried out in research uses deductive analysis, namely a method of thinking that begins with theories, postulates and general provisions and then draws specific conclusions. This research results in the conclusion that the pillars and conditions of the muraabahah contract in muraabahah financing at BSM Tanjungpinang have been fully fulfilled and in accordance with sharia provisions. Keyword: Bank Syari’ah Mandiri (BSM), Financial Institutions